Correlation of spinal flexors and extensors muscle power on waist hip ratio in collegiate - MALARVIZHI.D,; DHINESH.A.M,; VIDHYA.G,; SIVAKUMAR.V.P.R., (International Journal of Pharma and Bio Sciences, 2017)
People who are inactive are more likely to gain weight.Obesity is a worldwide epidemic and is characterized by excess adipose tissue. It contributes and early mortality.It is a disease characterized by excess body fat. .The phenomenon is global and about 30 million Indians are obeseThe objective of the study was correlation of spinal flexors and extensors muscle power on waist hip ratio in collegiate.TheStudy design wasNon-Experimental, Study type was observational. Inclusion criteria were both males and females, age between 17 to 22 years.100Subjects were selected according to inclusion and exclusion criteria. Outcome measures were Waist- Hip Ratio, muscle power of spinal flexors and extensors.There was positive correlation between spinal flexors and Waist-Hip Ratio (r = 0.078).But there was negative correlation between spinal extensor and waist hip- ratio (r = -0.025).The study concluded that when Waist-Hip Ratio increases abdominal musclepower decreases but extensors muscles power won’t changes with Waist- Hip Ratio.